Plant macro remains from Early Historic Vessel, Gilund, Rajasthan. (13th November 2013) - Naik, Satish S.; Shinde, Vasant; Sarkar, Amrita; McCormick, Megan Merry
The macrobotanical remains were recovered from the Early Historic vessel from Gilund, Rajasthan by employing dry and wet sieving techniques in the Palaeobotany laboratory. The retrieved archaeobotanical material was in carbonized and semi-carbonized state. It involves cultivated barley grains, a single cut grain of rice and a seeds of weed plant along with a bulk of wood charcoal pieces. These could survive in the carbonized state by being exposed to heat or fire. The impressions of grass leaves were found on well backed brickbats occurred in the vessel. Few molluscan shells were also retrieved during wet sieving .